Software engineering’s contribution to earthquake engineering (2013)
Earthquakes are natural disasters which affect Mexico regularly. It is very important to obtain all information about them quickly, in order to speed up attention to population affected and if it is possible, applying prevention actions. At present time, to obtain knowledge of seismic events is essential to use computer and specialized software. In this study 22 software applications for seismic analysis have been examined in order to define predominant characteristics, strengths and limitations, to provide current status of this particular field and generating lines of advance for new developments or prototypes. It shows clearly the existing technological dependency of this country as much in hardware as software. Therefore academic cooperation between different branches of engineering should be encouraged for the creation of new domestic products.